Early Bilateral Gonadoblastoma in a Patient with Mixed Gonadal Dysgenesis (Karyotype 45,X/46,XY): Case Report and Review of Literature - Trainavičius, Ignas; Dasevičius, Darius; Burnytė, Birutė; Kemežys, Robertas; Verkauskas, Gilvydas (Acta medica Lituanica, 2022)
Background: Mixed gonadal dysgenesis is a rare congenital and challenging condition, characterized mainly by 45,X/46,XY karyotype mosaicism, asymmetrical gonadal development and various internal and external genital anatomy. Because of frequent disorder of genital development and a higher risk of germ cell neoplasia, management of these patients is complex and requires multidisciplinary approach. Case: We present a 45,X/46,XY mixed gonadal dysgenesis patient diagnosed with gonadoblastoma in both gonads after bilateral gonadectomy at 1 year of age. Conclusions: Because of high risk for malignant transformation, gonadectomy of a streak-like gonad and biopsy with orchidopexy or gonadectomy of a dysgenetic testicle is recommended at an early age.